HIGHER EDUCATION AS SOCIAL DEVELOPMENT FACTOR - Ozarovska A.V. (Pressing Problems of Public Administration, 2017)
The article analyzes interrelation of education (an educated person), science (as a productive forceof society), and social production. The emphasis is laid on an increasingly more important role andplace of the social institute of higher education in the social progress and welfare of the population.